Cover Feature: Understanding the Nature of Solid‐Electrolyte Interphase on Lithium Metal in Liquid Electrolytes: A Review on Growth, Properties, and Application‐Related Challenges (Batteries & Supercaps 6/2021). Issue 6 (11th May 2021) - Nojabaee, Maryam; Kopljar, Dennis; Wagner, Norbert; Friedrich, Kaspar Andreas
Abstract : The Cover Feature illustrates the solid–electrolyte interphase (SEI) formed on lithium metal in contact with the liquid electrolyte and the consequential influence of this interlayer on the regulation of lithium dissolution and deposition. The stable SEI is of essence for the realization of practical lithium metal cells with enhanced cycle life. More information can be found in the Minireview by M. Nojabaee and co‐workers .